Simulation of a field condition to evaluate the risk of enrofloxacin-resistant Pasteurella multocida strain selection in food producing rabbits treated via drinking water - Circella, Elena; Lucatello, Lorena; Montanucci, Ludovica; Belloli, Chiara; Capolongo, Francesca (Frontiers in Veterinary Science, 2025)
IntroductionPasteurella multocida is a key bacterial agent involved in most respiratory disorders in rabbits. The objective of this study was to evaluate the risk of selecting Pasteurella multocida strains resistant to enrofloxacin (ENRO) in food producing rabbits treated with ENRO via drinking water, according to the standard husbandry practices. Indeed, despite the EU community guidelines recommend a prudent use of antibiotics and promote new strategies to prevent bacterial diseases, antimicrobial therapy remains the primary approach for pasteurellosis management in rabbits. Therefore, the potential risk of selecting resistant bacteria in food-producing animals requires identifying optimized dosage regimens to minimize resistance emergence and to extend the useful lifetime of the drug.MethodsIn this study, we isolated Pasteurella multocida strains from bacterial colonies sampled in nasal swabs collected from 6 healthy rabbits and 12 rabbits suffering respiratory disorders. Animals were sourced from industrial farms and were randomly selected to investigate the inter-individual variability in antimicrobial exposure associated with treatment via drinking water. Sick rabbits underwent an approved ENRO treatment (10 mg/kg for 5 days) administered via drinking water, following standard husbandry practices. We investigated the minimum inhibitory concentration (MIC), the minimum bactericidal concentration (MBC), and the mutant prevention concentration (MPC) of ENRO against bacterial strains in healthy rabbits and in sick rabbits before and after treatment. We recorded plasma drug concentrations of treated animals, and we applied the mutant selection window (MSW) approach to each subject. Finally, we calculated the PK/PD indices for concentration-dependent antimicrobials to assess ENRO’s clinical efficacy and it’s potential for promoting resistance using published pharmacokinetic (PK) parameters and maximum drug plasma concentrations recorded in this study.ResultsHere we showed that treatment with ENRO improved clinical signs in rabbits with pasteurellosis but failed to completely eradicate the pathogen, consistent with previous studies. MPC-based analysis showed acquired resistance and potential ENRO-induced shift to a lesser sensitivity in the P. multocida population. Moreover, MSW analysis revealed that 45% of treated rabbits exhibited potential for drug resistance selection.ConclusionThese findings suggest that the current ENRO dosing regimen for pasteurellosis in rabbits is inadequate and may contribute to resistance development.